2012
DOI: 10.1016/j.ijhydene.2011.07.046
|View full text |Cite
|
Sign up to set email alerts
|

The effects of halide modifiers on the sorption kinetics of the Li-Mg-N-H System

Abstract: The effects of different transition metal halides (TiCl 3 , VCl 3 , ScCl 3 and NiCl 2 ) on the sorption properties of the 1:1 molar ratio of LiNH 2 to MgH 2 are investigated. The modified mixtures were found to contain LiNH 2 , MgH 2 and LiCl. TGA results showed that the hydrogen desorption temperature was reduced with the modifier addition in this order: TiCl 3 > ScCl 3 > VCl 3 > NiCl 2 . Ammonia release was not significantly reduced resulting in a weight loss greater than the theoretical hydrogen storage cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Both samples exhibited the same reduction in dehydrogenation capacity seen in our previous work [30]. This reduced capacity was attributed the reduction in diffusion kinetics for the transition metal halide modified mixtures to the formation of lithium salts, irreversible Mg 3 N 2 formation, the loss of essential ammonia and the agglomeration of particles during the high temperature dehydrogenation [30].…”
Section: Isothermal Dehydrogenation/hydrogenation Cycling Of Unmodifisupporting
confidence: 75%
See 3 more Smart Citations
“…Both samples exhibited the same reduction in dehydrogenation capacity seen in our previous work [30]. This reduced capacity was attributed the reduction in diffusion kinetics for the transition metal halide modified mixtures to the formation of lithium salts, irreversible Mg 3 N 2 formation, the loss of essential ammonia and the agglomeration of particles during the high temperature dehydrogenation [30].…”
Section: Isothermal Dehydrogenation/hydrogenation Cycling Of Unmodifisupporting
confidence: 75%
“…This reduced capacity was attributed the reduction in diffusion kinetics for the transition metal halide modified mixtures to the formation of lithium salts, irreversible Mg 3 N 2 formation, the loss of essential ammonia and the agglomeration of particles during the high temperature dehydrogenation [30]. However, in this experiment, the reduction kinetics can be attributed to the favorable reaction between LiH and N to form Li 2 NH [37], essentially hindering the formation of necessary intermediate steps.…”
Section: Isothermal Dehydrogenation/hydrogenation Cycling Of Unmodifimentioning
confidence: 79%
See 2 more Smart Citations
“…Therefore, to improve the kinetics at temperatures lower than 200 • C, the reaction needed to be catalyzed with suitable dopants or additives. During the last years, many attempts have been made to improve the sorption kinetics of the 2LiNH 2 + MgH 2 system and, in this context, a large number of papers have been published [62][63][64][65][66][67][68][69][70][71][72][73][74]. Luo et al reported faster absorption kinetics by doping with less than 4 mol.…”
Section: Li-mg-n-h Systemmentioning
confidence: 99%